Killing time - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery, 2024)
"Beloved New York Times bestseller M. C. Beaton's cranky, crafty Agatha Raisin-the star of her own hit T.V. series-is back on the case again. Agatha Raisin's private detective agency is working flat out on a series of shop burglaries. The break-ins seem to have taken a violent turn when a friend of Agatha's is murdered during a raid on his shop. Although determined to nail the villains, Agatha still makes time to help Sir Charles Fraith prepare to stage a massive, hugely glamorous, promotional event in the grounds of his ancestral home, Barfield House. When Agatha begins to receive death threats and narrowly avoids being abducted by kidnappers, she takes advantage of a previously arranged trip to Mallorca to lie low for a while. There she meets her partner, former police officer John Glass, who is now working as a dance instructor on a cruise liner. Their relationship founders over John's apparent closeness to his stage dance partner, Louise. Putting her love life on hold, Agatha heads home, having worked out who has been threatening her life. Can Agatha track down whoever it is that wants her dead, nail her friend's murderers and rescue her romance with John Glass? Everything comes to a climax at the Barfield Extravaganza when Agatha also manages to solve a 400-year-old Cotswold murder mystery!"--